Criminal Legality Affecting Cybercrimes in Yemen - Nazli, Ismail@Nawang; Hussin@Mohamad, Ab Rahman; Ammar Abdullah Saeed, Mohammed (2017)
Criminal legality is a principle that promotes justice and stability. A judge cannot criminalise or expand the interpretation of any existing laws to criminalise new actions or offences that are not provided by the legislature. Article 47 of the Yemeni Constitution 1990 states that “No crime or punishment shall be undertaken without a provision of Shari’ah or law”. Further, section 2 of the Yemeni Penal Code 1994 states that “crime and punishment must be defined by law as such”. Unfortunately, cybercrime is one of the new offences that are not specifically regulated by Yemeni laws. Since cybercrime is one of the greatest threats facing international community, this paper attempts to examine the criminal legality affecting cybercrime in Yemen. This study is a purely doctrinal legal research and data were collected from both primary and secondary sources like books, articles, legal doctrines, statutes and many others. To sum up, Article 47 of the Yemeni Constitution 1990 and section 2 of the Yemeni Penal Code 1994 generally cover traditional offences that are committed on the Internet and via computer such as online pornography and online defamation. Nonetheless, serious issues arise with regard to new offences that can only be committed in the cyber world such as hacking and spamming as they are nowhere provided in the Yemeni legal framework.